Human development – sustainable development – progress: an attempt at rural change - Gorlach, Krzysztof; Klekotko, Marta; Nowak, Piotr (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2013)
The authors attempt a critical analysis and elaborate the concepts of development and progress put forward by Jan Szczepański. With regard to Social Development the authors have focused on the idea of culture as a factor of development as it had been proposed by Szczepański. They broaden Szczepanski`s perspective in which culture might be conceptualized as a developmental factor only when there is “physical” contact between different cultures and societies. Addressing the issue of progress the authors try to overcome one of the most important weaknesses of Szczepanski`s analytical frame, namely: the lack of clear criteria for an assessment of which type of human development might be treated as the human progress. According to their opinion such criteria might be found in ten principles of sustainable development. Such rather general remarks are supplemented with a few examples from rural development issues. In conclusion, two basic arguments supporting a statement about sustainable development as progress are formulated. Firstly, sustainable development is an integral and complex type of change affecting the economy, natural resources, society and culture. Secondly, sustainable development has been focused on more than just economic growth, preservation of natural resources as well as social fabric and cultural diversity, but also on mechanisms and instruments of social change, such as: social agency, governance or anticipation of possible negative effects resulting from formulation and implementation of developmental policies.
Keywords: human development; progress; sustainable development; culture; rural areas